Optimasi Penjadwalan Shift Jaga Dokter di IGD Menggunakan Algoritme Genetika (Studi Kasus Rumah Sakit di Malang) - Annisaa Amalia Safitri; Imam Cholissodin; Lailil Muflikhah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Emergency room (ER) is one of the units in a hospital who the first of receiving patients in case of an emergency. In ER, there are doctors who should be available for 24 hours to deal with patient who come everytime when an emergency form happen. To keep the performance of doctors who working 24 hours in ER, then we make a schedule that use with shift system. For 1 month scheduling, 11 doctors will split into 3 shift work in a day. In order to optimize and make the best combination in doctor's schedule at ER, then made the doctor's scheduling system in a ER using genetic algorithm. Reproductive process using 2 ways, first the process of crossover by using extended intermediate crossover and second the mutation process by using a reciprocal exchange mutation, and then will use the last process of algorithm and the name is elitism selection process. Testing that is used for doctor's scheduling system in a ER is there are 3 types of testing. The first test is testing the number of popSize, with the highest fitness at a value of 40 with an average of 1,766, the second test is testing the value of generation with the highest fitness at generation value 40 with an average value of fitness 1,608, and the last test is combination of cr mr with the highest fitness value on a combination of 0,7 and 0,3 with average fitness 2,064. From those results, do more testing to compare the fitness value of fitness values of the system with real data provided by the hospital. And the results show that the value of fitness of the system = 11,111 is greater than the value of the data on real fitness given hospital = 7,692.